THE UTILIZE OF SOCIAL MEDIA IN EDUCATION WRITING SKILLS - Aqsha Dinanti; Aisyah Purnama Nst, Juni Dara Pratiwi Sinaga, Najwa Kamila Harpan, Nesa Romuwilda Pasaribu, Mutia An (International Journal of Teaching and Learning, 2024)
Social media is a product of information and communication technology used by many people around the world, from children to adults. Although not created specifically for educational purposes, social media have attracted the attention of some educators, especially in the field of English teaching and learning. The objective of this study is to find out the types of social media used by English department students in the first semester of UNIMED and the use of social media in learning English writing. This study was conducted using a descriptive- qualitative design. The researcher used questionnaires, interviews, and documents as tools to collect data. The primary data in this research was obtained from questionnaires and interviews with the students who were active in using social media in learning English writing. Then, the secondary data contained recordings and documentation obtained from the students as the subjects of this research. The data analysis techniques used were data condensation, data display, conclusion drawing, and verification. To test the validity of the data, the researcher used the credibility technique with the source triangulation method. The result of this research showed that there were seven types of social media used by the students in learning English writing, namely Facebook, Twitter, Instagram, YouTube, WhatsApp, Web blog, Wikipedia. Students mainly use social media to learn English writing using a number of features provided, including allowing them to interact with friends such as individual chats, group chats, comment sections, captions, descriptions, history and biography. Additionally, they also use some of these social media as learning resources to help them develop their English writing skills.